2021
DOI: 10.1038/s41598-021-99268-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Male Specific Lethal complex and genomic imbalance on global gene expression in Drosophila

Abstract: The inverse dosage effect caused by chromosome number variations shows global consequences in genomic imbalance including sexual dimorphism and an X chromosome-specific response. To investigate the relationship of the MSL complex to genomic imbalance, we over-expressed MSL2 in autosomal and sex chromosomal aneuploids, and analyzed the different transcriptomes. Some candidate genes involved in regulatory mechanisms have also been tested during embryogenesis using TSA-FISH. Here we show that the de novo MSL comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 72 publications
2
22
0
Order By: Relevance
“…Among these human aneuploidies, we found that in trisomy 18 a large subset of cis genes was closer to dosage compensation, and the trans modulations were primarily inversely affected (Figure 1C,D), which were validated by differential gene expression analysis (Figure 1J-R). This observation indicates that the trans genes showing an inverse dosage effect and the cis genes predisposed to compensation are likely affected by related mechanisms as previously found (Birchler et al, 1990; Hou et al, 2018; Shi et al, 2021; Yang et al, 2021; Zhang S et al, 2021a). To investigate whether the dosage compensated genes on each chromosome were refractory to modulation, we generated trans distributions for the expression of cis compensated genes (DC genes; ratios between 0.9 and 1.1) identified in each trisomy for an effect by the other trisomies (Figure 2A-F).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Among these human aneuploidies, we found that in trisomy 18 a large subset of cis genes was closer to dosage compensation, and the trans modulations were primarily inversely affected (Figure 1C,D), which were validated by differential gene expression analysis (Figure 1J-R). This observation indicates that the trans genes showing an inverse dosage effect and the cis genes predisposed to compensation are likely affected by related mechanisms as previously found (Birchler et al, 1990; Hou et al, 2018; Shi et al, 2021; Yang et al, 2021; Zhang S et al, 2021a). To investigate whether the dosage compensated genes on each chromosome were refractory to modulation, we generated trans distributions for the expression of cis compensated genes (DC genes; ratios between 0.9 and 1.1) identified in each trisomy for an effect by the other trisomies (Figure 2A-F).…”
Section: Resultssupporting
confidence: 80%
“…At the same time, the expression of some genes encoded by the varied chromosomes did not change with the gene dosage; in other words, they were compensated (Birchler, 1981; Birchler and Newton, 1981; Guo and Birchler, 1994). In Drosophila , both autosomal and sex chromosome aneuploidies can affect the expression levels of other chromosomes, while the transcription of the varied chromosome is closer to normal diploid levels (Devlin et al, 1982, 1988; Birchler et al, 1990; Sun et al, 2013a,b,c; Zhang S et al, 2021a). Recent whole-genome studies of maize and Arabidopsis aneuploid series have also demonstrated the prevalence of the inverse dosage effect and dosage compensation (Hou et al, 2018; Johnson et al, 2020; Shi et al, 2021; Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Polytene chromosomes from the third instar larvae were dissected, fixed, and processed for antibody staining according to reference [ 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…The primers containing flanking T3 and T7 promoter elements are listed in Table S1 . Detailed experimental steps are as described by Zhang S, et al [ 62 ], and Le’cuyer et al [ 63 ].…”
Section: Methodsmentioning
confidence: 99%
“…To detect segmental duplications, common repeats of the genome must be removed from the analysis (Pu et al 2018) which was a critical aspect of our probe design. Segmental duplications are long (> 1 kilo-base pairs) and similar (90-100%) sections of DNA sequences that are located in multiple locations in the genome and are hotbeds for the emergence of new In the inverse situation, the expression effect can act across the genome and not just impact the chromosome that was modi ed (Zhang et al 2021). In yeast cells that were tested by the addition of yeast arti cial chromosomes containing mostly intronless genes, the mere presence of additional DNA generated a positive dosage response correlated with the number of additional yeast genes, and the imbalance led to a stress response aimed at restoring the wildtype physiology (Torres et al 2007).…”
Section: Putative Segmental Duplicationmentioning
confidence: 99%